دور التدريب في رفع كفاءة الأداء دراسة ميدانية لشركة العامة للمياه والصرف الصحي (طرابلس) (Comprehensive Journal of Science, 2025)
The main objective of this study is to identify the role of training in improving performance efficiency among employees of the General Company for Water and Wastewater in Tripoli. To achieve this goal, the researcher prepared a questionnaire that was distributed to a stratified random sample comprising (15%) of the study population. This study found a strong and statistically significant effect of training on enhancing performance efficiency through the following elements: training programs, the effectiveness of training programs, and lack of resources. It also found a very strong and positive relationship between training and development and performance efficiency, indicating that the more attention is given to training programs, the higher the levels of efficiency among employees.
Keywords: Training, performance, performance efficiency, training elements, General Company for Water and Wastewater